2014
DOI: 10.15580/gjss.2014.3.010614020
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Mining on the Natural Environment and Wellbeing of Mining-Fringe Communities in Prestea, Ghana

Abstract: Although Small Scale surface mining has grown significantly in the developing world in recent decades, the hive of environmental and socioeconomic discontents that accompanies large-scale surface mining activities are very much unprecedented. This paper therefore examines the operations of large scale mining group in the context of such discontents, in the case of Prestea, a vibrant mining town in the Prestea-Huni Valley District Assembly Area in the Western Region of Ghana. Case study approach within a natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In communities like New Longoro, Bamboi and Bungase, responses from the questionnaires and the FGDs showed that the emerging logging, and especially gold mining, is resulting in low attendance and high dropout rates at school as a result of pupils leaving school to work and some of the girls getting pregnant and leaving school. Low enrolment and attendance rates at school, as well as dropout rates, have been reported in mining areas in Ghana and elsewhere in the sub‐region (see e.g., Owusu and Dwomoh, ; Erdiaw‐Kwasie et al , ; O’Neill, ).…”
Section: Resultsmentioning
confidence: 97%
“…In communities like New Longoro, Bamboi and Bungase, responses from the questionnaires and the FGDs showed that the emerging logging, and especially gold mining, is resulting in low attendance and high dropout rates at school as a result of pupils leaving school to work and some of the girls getting pregnant and leaving school. Low enrolment and attendance rates at school, as well as dropout rates, have been reported in mining areas in Ghana and elsewhere in the sub‐region (see e.g., Owusu and Dwomoh, ; Erdiaw‐Kwasie et al , ; O’Neill, ).…”
Section: Resultsmentioning
confidence: 97%
“…Mining is considered to be an essential economic activity which contributes significantly to the development of several economies (Erdiaw-Kwasie et al , 2014). Every mining project goes through different phases, beginning with initial exploration, to the mineral exploitation and the final post-closure phase (Akabzaa and Darimani, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, underground mining results in environmental subsidence. Erdiaw-Kwasie et al (2014) report that the physical environment of communities where large-scale surface mining activities take place are characterized by poor vegetation, noise, vibrations and acidic rains which causes cracks buildings.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold, diamond, bauxite, and manganese are the main minerals produced by large-scale mining companies in the country. Other industrial minerals, like silver, salt, and limestone, are produced by small-scale operators [ 14 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%